Efficiency of the Crile Procedure in the Removal of Thyroid Malignancies Invaded into the Internal Jugular Vein - Deineko, Illia (International Journal of Statistics in Medical Research, 2023)
Aim: This work aims to determine the effectiveness of the Crile procedure for optimizing the diagnosis and treatment of patients with locally advanced thyroid malignancies. Objects: The objects of the study were the results of treatment of patients with thyroid cancer using two techniques: Crile procedure and vein resection with sealing and preservation of blood flow. Materials and Methods: The research was carried out experimentally using Crile surgical intervention and vein resection with sealing and preservation of blood flow. The effectiveness of the treatment was assessed by observing the recurrence and mortality rates. The patient’s quality of life was assessed through the conversation and questionnaire survey. Results and Findings: It was found that Doppler ultrasonography of the main vessels in the neck helps to establish the internal jugular vein invasion, as well as its tumour thrombosis at the preoperative stage in clinical cases of suspected extrathyroidal extension of thyroid tumours in addition to radiological methods. A thyroid gland with a tumour invaded into the internal jugular vein must be radically removed with simultaneous resection of the affected part of the vein. We proved that the Crile procedure — resection of a vein with sealing of stumps and interruption of blood flow on one side of the neck — is a safe technique. It reduces the trauma and duration of the operation and reduces the likelihood of recurrence as it does not require further plastic surgery or vascular shunting with the restoration of blood flow. At the same time, bilateral interruption of blood flow in cases of resection of both internal jugular veins can lead to serious complications and requires a blood flow restoration operation from the side of the smaller tumour invasion.